2019
DOI: 10.1371/journal.pone.0216371
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of self- and graft-incompatibility traits in an F1 apricot progeny

Abstract: Floral self-incompatibility affecting yearly yield in a weather-dependent manner and graft incompatibility affecting longevity of mature trees are two important traits for apricot production. However, genetic control of graft compatibility and relationship between these traits are unknown. Here, we analyzed its inheritance in an F 1 apricot progeny from a cross between self- and graft- incompatible and self- and graft-compatible cultivars. Hybrid individuals were genotyped for establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…To generate a hybrid plant material for genetic analysis, we cross-pollinated two apricot cultivars that were previously phenotyped as graft-compatible and -incompatible when grafted to the same rootstock universal for Prunus. Using this cross, we established a phenotyping protocol for this complex trait based on cytomorphological observations of graft interface (Irisarri et al, 2019). Regression analysis of phenotypic data across the progeny revealed likely polygenic control of successful graft formation.…”
Section: Introductionmentioning
confidence: 99%
“…To generate a hybrid plant material for genetic analysis, we cross-pollinated two apricot cultivars that were previously phenotyped as graft-compatible and -incompatible when grafted to the same rootstock universal for Prunus. Using this cross, we established a phenotyping protocol for this complex trait based on cytomorphological observations of graft interface (Irisarri et al, 2019). Regression analysis of phenotypic data across the progeny revealed likely polygenic control of successful graft formation.…”
Section: Introductionmentioning
confidence: 99%
“…However, phenotyping graft compatibility in large populations is challenging as it requires grafting many (hundreds) individuals to accurately score this trait, which has many logistical problems. To begin to overcome these problems, recently graft union formation was assessed at 1 month and 1 year after grafting by scoring the necrotic line, and wood and bark discontinuity, and cellular arrangements at the interface in a bi-parental F1 apricot scion population grafted onto a plum rootstock (Irisarri et al, 2019 ). Continuous variation was found in the graft union traits scored (Irisarri et al, 2019 ); this study paves the way for further studies into the genetic control of graft union formation.…”
Section: Discussionmentioning
confidence: 99%
“…To begin to overcome these problems, recently graft union formation was assessed at 1 month and 1 year after grafting by scoring the necrotic line, and wood and bark discontinuity, and cellular arrangements at the interface in a bi-parental F1 apricot scion population grafted onto a plum rootstock (Irisarri et al, 2019 ). Continuous variation was found in the graft union traits scored (Irisarri et al, 2019 ); this study paves the way for further studies into the genetic control of graft union formation. However, understanding the genetic basis of graft incompatibility would be greatly accelerated if marker metabolites or transcripts could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these grape receptor kinase genes included homologs of S-locus glycoprotein-like gene family. Nevertheless it is important to note that in spite of these general similarities Irisarri et al (2019) found no correlation between GSI and graft compatibility in the analysis of an apricot (Prunus armeniaca) F 1 segregating population.…”
Section: Si and Other Self/non-self Discrimination Systemsmentioning
confidence: 93%